A COMPARATIVE STUDY OF THE BEHAVIOUR OF ANTIRRHINUM MAJUS SPECIES CULTIVATED IN FIELDS AND IN VERTICAL SYSTEMS FOR GREEN FAÇADES UNDER THE CLIMATE CONDITIONS IN THE NORTH-EASTERN REGION OF ROMANIA - Mirela COJOCARIU; Elena Liliana CHELARIU; Ciprian CHIRUŢĂ; Petronica AMIŞCULESEI; Andromeda Cristina SONEA (Journal of Applied Life Sciences and Environment, 2022)
A highly popular and well-known flowering species for the unmistakable shape of its velvety and beautifully coloured flowers, Antirrhinum majus is often used in garden decor due to its long flowering period, ease of cultivation and low maintenance during the growing season. This study aims to investigate the behaviour of a dwarf variety of the Antirrhinum majus species grown in both vertical systems for green façades and also in a control field under the climate conditions in the north-eastern region of Romania. The façades of the vertical structure were been oriented towards a cardinal point, each of them having four equal layers arranged on height. The study found that this dwarf variety adapts very well to vertical systems, maintaining its ornamental features for a long time. During the experiment, observations included the diameter, height and number of flowers per plant in the control variant and on each side of the experimental structure. The highest values in July and August for plant diameter, plant height and the number of flowers were shown for the western facade and the lowest for the control variant. Instead, the control variant in September held the first position showing the highest means for all three monitored parameters and the lowest were for the southern orientation.